Temporal Trends in Healthcare Costs and Outcome Following ICU Admission After Traumatic Brain Injury. Issue 4 (April 2018) - Raj, Rahul; Bendel, Stepani; Reinikainen, Matti; Hoppu, Sanna; Luoto, Teemu; Ala-Kokko, Tero; Tetri, Sami; Laitio, Ruut; Koivisto, Timo; Rinne, Jaakko; Kivisaari, Riku; Siironen, Jari; et al.
Abstract : Objective: To assess temporal trends in 1-year healthcare costs and outcome of intensive care for traumatic brain injury in Finland. Design: Retrospective observational cohort study. Setting: Multicenter study including four tertiary ICUs. Patients: Three thousand fifty-one adult patients (≥ 18 yr) with significant traumatic brain injury treated in a tertiary ICU during 2003–2013. Intervention: None. Measurements and Main Results: : Total 1-year healthcare costs included the index hospitalization costs, rehabilitation unit costs, and social security reimbursements. All costs are reported as 2013 U.S. dollars (). Outcomes were 1-year mortality and permanent disability. Multivariate regression models, adjusting for case-mix, were used to assess temporal trends in costs and outcome in predefined Glasgow Coma Scale (3–8, 9–12, and 13–15) and age (18–40, 41–64, and ≥ 65 yr) subgroups. Overall 1-year survival was 76% ( n = 2, 304), and of 1-year survivors, 37% ( n = 850) were permanently disabled. Mean unadjusted 1-year healthcare cost was 39, 809 (95% CI, 38, 144–41, 473) per patient. Adjusted healthcare costs decreased only in the Glasgow Coma Scale 13–15 and 65 years and older subgroups, due to lower rehabilitation costs. Adjusted 1-year mortality did not change in any subgroup ( p < 0.05 for all subgroups). Adjusted risk of permanent disability decreased significantly in all subgroups ( p < 0.05). Conclusion: During the last decade, healthcare costs of ICU-admitted traumatic brain injury patients have remained largely the same in Finland. No change in mortality was noted, but the risk for permanent disability decreased significantly. Thus, our results suggest that cost-effectiveness of traumatic brain injury care has improved during the past decade in Finland. Abstract : Supplemental Digital Content is available in the text.